Pengembangan Media Audio Visual Berbasis Sparkol Videoscribe Pada Tema 4 Sehat Itu Penting Kelas V SDN 101777 Saentis - Butarbutar, Shanty Teresia; Simanjuntak , Sorta; Arifin Siregar; Simanungkalit , Erlinda; Gandamana, Apiek (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research purpose to determine the feasibility, practicality, and effectiveness of using Sparkol Videoscribe based audio visual media in theme 4 being healthy is important class V at SDN 101777 Saentis school year 2022/2023. The type of this research is R&D (Research and Development) by using ADDIE model through 5 stages that is Analysis, Design, Development, Implementation, dan Evaluation. The subjects of this study were all students in class Vb SDN 101777 Saentis that contains 32 students. Data collection techniques using interview, questionnaires, and test. Feasibility assessment is obtained from the result of material and media validation by PGSD FIP UNIMED lecturers, practically assessment is obtained from the teacher’s assessment by filling in the practically instrument carried out by class V teachers at SDN 101777 Saentis and effectiveness assessment is obtained from the tests carried out by class V student at SDN 101777 Saentis. The results of media research developed showed sparkol Videoscribe audio visual media was stated to be very feasible with a score of 90% for material experts and 87% for media experts. Sparkol Videoscribe audio visual media was stated to be very practical to apply with a score 92% for Class V teacher assessment SDN 101777 Saentis. Student responses did the pre-test and post-test when field trial using Sparkol Videoscribe based audio visual media were declared effective with an N-gain score of 0,8003 with percentage of 80%. The conclusion is that Sparkol Videoscribe based audio visual media that has been developed is very feasible, very practical, and effective